Synthesis of cyclic polylactide catalysed by bis(salicylaldiminato)tin(ii) complexes - Parichat Piromjitpong (2018)
Eight bis(salicylaldiminato)tin(ii) complexes have been synthesized from the reaction of Sn[N(SiMe 3 ) 2 ] 2 and 2 equiv of the corresponding ligands at room temperature. The ligands, synthesized from salicylaldehyde and amines, were designed to have different electronic and steric properties using different amines to synthesize the tin(ii) complexes as aniline (2a), 2,6-dimethylaniline (2b), 2,6-diisopropylaniline (2c), 4-methoxyaniline (2d), 4-trifluoromethylaniline (2e), methylamine (2g), and tert-butylamine (2h). Ligand variation at the salicyl group synthesized from 4-bromosalicylaldehyde and 2,6-diisopropylaniline was used to form complex 2f. Complex 2c was characterized crystallographically. All catalysts were active for the neat polymerization of l-lactide at 115 °C. At a lactide:Sn molar ratio of 10:1, cyclic polylactide (PLA) was obtained as demonstrated by 1 H NMR and mass spectrometry. Addition of 1 equiv of benzyl alcohol in the polymerization produced linear PLA. At a higher lactide:Sn molar ratio of 200:1, high molecular weight PLAs with M n up to 132200 Daltons were obtained. Results from GPC coupled with light scattering detector and viscometer suggested that they are cyclic PLA. The order of reactivity based on conversion was determined to be 2c < 2b < 2a in accordance with lower steric hindrance. For electronic contribution, the order of 2e < 2a < 2d was observed in agreement with the increasing electron donation of the ligands. Complex 2g having the smallest substituents was found to be the most active catalyst. © 2012 The Royal Society of Chemistry.